Executive functions and attention in school-age children according to the behavioral profile rated by their teachers - Arán Filippetti, Vanessa (2013)
The present study aimed at analyzing the link between school-age children's performance in neuropsychological tests that examine the executive function (EF) and attention, and their behavioral profiles (i.e., Attention Deficit (AD) and Hyperactivity (HA), as rated by their teachers. For the assessment of EF and attentional mechanisms, different tasks were administered to a sample consisting of 124 children from 3rd to 6th grade. In addition, teachers from each grade completed a behavior rating scale for every child. Bifactorial MANCOVA was used in order to analyze the effect of both AD and HA factors, controlling for the intelligence, over the child's cognitive performance. Results demonstrated significant differences according to AD level in tasks that assess (i) selective attention, (ii) working memory, (iii) reactive cognitive flexibility (iv) verbal fluency and (v) reflexivity-impulsivity. Conversely, regarding the HA level, results showed significant differences only in terms of the number of errors made in the MFFT20. This work provides evidence on the relationship between children's behavior within the school setting and their cognitive performance.